Artikel Riview: Pengaruh Penggunaan Matriks Pada Tablet Lepas Lambat - Maulina Apriani; Dian Ayu Oktavia; Isnaini Sukmaning M; Dila Alvia Rahmasari; Zahwa Natasya Novita P; Alvito Syawal Z; Dewi Rahmawati; Dzakiya Zhihrotulwida; Yani Ambari; M. Fithrul Mubarak (Lembaga Pengembangan Kinerja Dosen, 2025)
Sustained-release tablets are pharmaceutical preparations designed to gradually release the active substance over a specific period, thereby maintaining a constant concentration of the drug in the circulatory system and enhancing therapeutic effectiveness.The development of sustained-release tablets aims to extend the duration of drug action, reduce the frequency of dose administration, and minimize fluctuations in drug levels in the plasma, which ultimately enhances patient compliance and treatment effectiveness, especially in chronic diseases.The purpose of this review is to identify various formulation methods and innovations in the production of sustained-release tablets, as well as to examine the factors that influence the success of these formulations.The method used in this study is a literature review that collects data from various scientific publications over the past five years through online platforms such as Google Scholar, using keywords related to matrix sustained-release tablets and pharmaceutical formulations.The results of the review indicate that various techniques, such as formulating polymer matrices, coating, and encapsulation, have been applied with varying degrees of success depending on the type of active ingredients and excipients used. Some formulation innovations, such as the use of natural polymer matrices and matrix modifications, have proven effective in achieving controlled, stable, and quality-standard-compliant drug release.